2022
DOI: 10.1021/acs.iecr.2c00077
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and Mass Transfer Characteristics for Extractive Desulfurization of Diesel Using Highly Viscous Ionic Liquids in Microchannels: The Effect of the Phase Ratio and Temperature

Abstract: Microreactor technology shows great potential in the enhancement of liquid−liquid mass transfer, which is important especially when highly viscous fluids are involved. This provides an attractive way to intensify the extractive desulfurization (EDS) using ionic liquids (ILs) as an effective technique for ultralow-sulfur diesel production. This work concerns the extraction of dibenzothiophene in model diesel by [BMIM]PF 6 in a microchannel. The effects of the phase ratio and temperature on the hydrodynamics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The statistical results presented in Table 2 show that the volumetric ratio was the most important variable of the experimental design employed. As shown by Ji et al, 4 Karamzadeh et al, 11 and Al-Azzawi et al, 20 the increase in the volumetric ratio (proportion between solvent and fuel) results in an increase in the interfacial area, providing more opportunities for the interaction between sulfur contaminants and solvents, leading to higher process efficiencies. This type of behavior was widely discussed by Jin et al 30 in which the authors used a mathematical formulation based on global mass transfer equations, exposing physical behaviors in microsystems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical results presented in Table 2 show that the volumetric ratio was the most important variable of the experimental design employed. As shown by Ji et al, 4 Karamzadeh et al, 11 and Al-Azzawi et al, 20 the increase in the volumetric ratio (proportion between solvent and fuel) results in an increase in the interfacial area, providing more opportunities for the interaction between sulfur contaminants and solvents, leading to higher process efficiencies. This type of behavior was widely discussed by Jin et al 30 in which the authors used a mathematical formulation based on global mass transfer equations, exposing physical behaviors in microsystems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3 The presence of sulfur-rich compounds in fuels causes a series of industrial and environmental problems, such as corrosion phenomena in petrochemical plants, poisoning, or deactivation of catalysts used in the treatment of crude oil. 4 Catalytic hydrodesulfurization (HDS) is a conventional technology for removal of sulfur compounds in the petrochemical industry. The process takes place in a fixed-bed reactor operating under severe conditions of temperature (573.2−673.2 K) and pressure (3.5−7.0 MPa) in the presence of bimetallic catalysts (Co−Mo or Ni−Mo).…”
Section: ■ Introductionmentioning
confidence: 99%
“…There was a flow of 0.01 to 1 µL/s 74) . There are numerous more processes that utilise microchannels to produce droplets and generate bubbles [337][338][339][340][341][342][343][344][345][346][347][348][349][350][351] . Chu and colleagues (2010) created bent rectangular tubes.…”
Section: Microchannels Used In Creation Of Bubbles and Dropletsmentioning
confidence: 99%
“…The main flow patterns observed in the microchannels are the slug flow, the droplet flow, the annular flow, and the parallel flow. Based on our knowledge, there are fewer investigations on the flow pattern maps of liquid–liquid flow in microchannels compared to gas–liquid flow. Moreover, as reported in Table , there is a lack of information on the flow pattern of the EDS process in the microchannels. , It should be noted that the previous articles did not provide a sufficient illustration of the various flow regime types. Additionally, the application of RSM for the optimization of the EDS in microchannels is limited to the study of Al-Azzawi et al To fill this research gap, the main focus of the present study is to employ the RSM for the optimization of EDS in the microchannels, considering the sulfur removal and appropriate flow pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the plug flow, the drop flow, the intermittent flow, and the annular flow were observed in different conditions, including mixture velocity, fuel to DES volume ratio, microchannel diameter, and different junction types. Ji et al 38 observed the slug flow, droplet flow, and irregular flow in the fuel/ionic liquid two-phase system in the microchannel at different flow ratio and temperature conditions. Santiago et al 39 reported the slug and droplet flow pattern in a microchannel contactor applied for the EDS process.…”
Section: Introductionmentioning
confidence: 99%